A working prototype to promote the creation and control of knowledge in supply chains. (27th January 2010) - Lopez, Gabriela; Eldridge, Steve
This paper describes an approach which uses the current Knowledge Management (KM) theory and technology to improve the dissemination of best practices among supply chain practitioners. Currently, a great deal of information on best practices is available to practitioners, but this potential 'information overload' can obscure possible unfavourable impacts of implementing so-called best practices in inappropriate contexts. This could well be because practitioners are simply unaware of these unfavourable impacts, but also because the information itself is largely unstructured. Consequently, practitioners face the time-consuming task of differentiating between the complexities of symptoms and problems associated with particular supply chain contexts. The research focuses on the management of supply chain knowledge with a particular emphasis on the quantification and dissemination of impacts from existing information on best practices. From this research, a multi-user collaborative working prototype is presented. In particular, a diagnosis module is designed and incorporated in the prototype to examine user-specified practices and to report back to the user concerning the possible impacts from these practices. This diagnosis module is then developed further to enable a formalised means to facilitate the generation and control of knowledge in supply chains.